Kelekatan antara Ibu dan Bayi Berhubungan dengan Pertumbuhan dan Perkembangan di Wilayah Kerja Puskesmas Desa Cabean - Erna Zuliyana; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Attachment is a form of mutually beneficial emotional relationship between mother and baby. There is poor attachment caused by inappropriate parenting patterns from parents. Good parenting patterns can stimulate spiritual, intellectual, emotional, moral, and social development, so that infant growth can run optimally. The purpose of this study was to determine the relationship between maternal attachment and infant growth and development in the work area of the Cabean Village Health Center. This study is quantitative, with a descriptive analysis approach and using a cross-sectional method. Data collection was carried out through questionnaires. There were 139 respondents taken using the total sampling method. The analysis used was the Gamma test. From the analysis of respondent data, it was found that there were an average of 85 male babies. The majority of mothers’ ages were in the range of 26-35 years with a percentage of 56.8%, and multiparity parity reached 61.9%. Most of them had education up to junior high school level as much as 42.4%, and most worked as housewives with a percentage of 66.2%. The results of the gamma test showed that there was a relationship between maternal attachment and infant growth and development, where maternal attachment to infant growth had a p-value (BB = 0.000, PB = 0.001), while attachment to infant development showed a p-value (0.000) with (OR = 0.555 and 0.613 CI = 0.726). This means that there is a significant relationship between maternal attachment and infant growth and development in the work area of the Cabean Village Health Center (p-value <0.05).